KBa3M2F14Cl (M = Zr, Hf): novel short-wavelength mixed metal halides with the largest second-harmonic generation responses contributed by mixed functional moieties - Yan, Mei; Chun-Li, Hu; Ru-Ling Tang; Wen-Dong, Yao; Liu, Wenlong; Sheng-Ping, Guo (Chemical science (Cambridge), 2024)
The development of short-wavelength nonlinear optical (NLO) materials is indispensable and urgently required for further applications. Halides have been disregarded as potential NLO materials with deep-ultraviolet (DUV) cutoff edges due to their weak second-harmonic generation (SHG) response and poor birefringence. Here, two novel and isostructural halides, KBa3M2F14Cl (M = Zr (KBZFC), Hf (KBHFC)), possess structures that are formed by isolated MF7 monocapped triangular prisms and dissociative K+, Ba2+, and Cl− ions. Compared with reported metal halides that are transparent to the DUV region, KBZFC and KBHFC possess the strongest SHG responses (approximately 1, 0.9 × KH2PO4), which are contributed by the synergistic effect of MF7 (M = Zr, Hf) groups, Ba2+ cations, and Cl− ions. The zero-dimensional structures favour sufficient birefringences (0.12, 0.10 @ 1064 nm) for phase-matchable (PM) behaviours. The discovery of KBZFC and KBHFC showcases the potential of NLO mixed metal halides transparent to the DUV region.